Shamanism with a drum among the Khanty of the Surgut Ob River region in the beginning of the 21st century - Rud’ A.A. (Вестник археологии, антропологии и этнографии)
The area of this research is confined to the Surgut Ob River region and includes the western and central areas of residence of the Eastern Khanty. The purpose of this work is to summarize and analyse information about the current state of shamanism with a tambourine among the Surgut Khanty. The main sources for the study were the author's field materials collected in 2002–2017 in the regions along the rivers of Lyamin, Pim, Tromyegan, Agan, Bolshoy and Maly Yugan. The uniqueness of the situation among the Surgut Khanty lies in the fact that the traditional rituals, which received a second wind in the 1990s in the wake of the actualization of ethnicity, in fact, were not interrupted. Among the traditional rites of the region, shamanism with a tambourine is one of the little-studied aspects of their spiritual culture. The article characterizes the current state of shamanic rituals with a tambourine, indicates the area of distribution of these practices, considers examples of making a tambourine and the formation of a shamanic gift, makes a description of the formal side and indicates the presently recorded occasions for the ritual. The differences between shamanism with a tambourine among the Khanty of the right bank and the left bank of the Ob River are revealed, and some aspects of shamanism are compared with those of the neighbouring ethnic groups.